1971
DOI: 10.1161/01.cir.43.5s1.i-105
|View full text |Cite
|
Sign up to set email alerts
|

Emergency Aortocoronary Bypass for Impending or Extending Myocardial Infarction

Abstract: Emergency coronary arteriography and aortocoronary bypass were successfully performed in three patients with preinfarction angina. Four patients with impending extension of a recent infarction died during or after aortocoronary bypass surgery. Aortocoronary bypass may improve angina and prevent infarction in selected instances of preinfarction angina. In patients with recent infarction and impending extension the risk of surgery appears to be prohibitively high.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
9
0
2

Year Published

1971
1971
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(11 citation statements)
references
References 0 publications
0
9
0
2
Order By: Relevance
“…Conflicting reports have been made concerning the influence of the timing of elective bypass surgery on perioperative morbidity and mortality [16][17][18]. Some authors have reported various timeframes for optimal surgical revascularization after ACS.…”
Section: Discussionmentioning
confidence: 99%
“…Conflicting reports have been made concerning the influence of the timing of elective bypass surgery on perioperative morbidity and mortality [16][17][18]. Some authors have reported various timeframes for optimal surgical revascularization after ACS.…”
Section: Discussionmentioning
confidence: 99%
“…Conflicting results with operative mortality ranging from 5 to 30% have been reported [2,[7][8][9]. Theoretical advantages or early intervention include limitation of both infarct expansion and adverse ventricular remodeling [2,10], as well as avoidance of an unnecessary waiting period.…”
Section: Discussionmentioning
confidence: 99%
“…Previous experimental studies aimed at increasing the oxygen supply to ischemic tissue by reopening an obstructe(l coronary arterv were disappointing in preventing the occurrence of subsequent mvocardial infarctionl, as discussed in (letail in the accompanying report ( 11). How-ever, the technique of aortocoronary bypass -ein grafting has proved promising clinically (16)(17)(18)(19)(20), and the question has again arisen as to the maximum timle interval durinig wliclh mivocardial cells distal to a coronary occlusion can resist ischemia and whether or not restoration of function can be accomplished. ' (4, 5.…”
Section: Discussionmentioning
confidence: 99%